Evaluation of wound-healing efficiency of a functional Chitosan/Aloe vera hydrogel on the improvement of re-epithelialization in full thickness wound model of rat. Issue 4 (November 2022) - Movaffagh, Jebreil; khatib, Majid; Fazly Bazzaz, Bibi Sedigheh; Taherzadeh, Zhila; Hashemi, Maryam; Seyedian Moghaddam, Atieh; Tabatabaee, Seyyed abbas; Azizzadeh, Mohammad; Jirofti, Nafiseh
Abstract: Objective: Chitosan-based hydrogels as wound dressings are expected to improve the efficiency of the wound-healing process. Fabrication of the composite structure of Aloe vera and biopolymeric hydrogels has been demonstrated to promote the wound-healing process through protection against a wide spectrum of microbes, and enhanced cell adhesion and differentiation. Therefore, the present study investigates to development of improved CHO/Aloe hydrogel for improving the wound-healing process in an animal model. Materials and methods: CHO hydrogel with Aloe was prepared, and its properties were evaluated in terms of viscosity, antibacterial activity, and ints In-vivo wound-healing efficiency in full-thickness wounds of rat models. Physical examination of wound-healing efficiency of CHO/Aleo hydrogel was evaluated by analyzing total wound closure, recovery percentage, and the epiderm thickness of wounds. Histological evaluation was performed using hematoxylin and eosin staining to evaluate the re-epithelialization, inflammatory response, granulation tissue formation, and fibrotic tissue formation. Results: The results showed a significantly higher wound-healing rate of the CHO/Aleo group compared to other groups at 3, 7, 14 days (p < 0.05). After 14 days of treatment, the best healing effect was observed in the CHO/Aleo gel with the highest tissue tension compared with other groups (p < 0.05). Histological findings indicated a significant difference in inflammatory response between control and treatment groups after three days of treatment (p < 0.05). Epidermal thickness was also significantly thicker in the CHO/Aleo gel group than others (p < 0.05). Conclusion: The present study an improved the effective topical drug-delivery system by CHO/Aloe hydrogel with the potential to reduce inflammation over time, allowing the body to recover more quickly and better re-epithelialization for improving the wound-healing procedures. Highlights: The Chitosan/Aloe vera hydrogel improvement the re-epithelialization in full thickness wound. Aloe vera promote the wound-healing process through enhanced cell adhesion and differentiation. Epidermal thickness is significantly thicker in the CHO/Aleo gel group compare to silver sulfadiazine as positive control.